Principle of Neutrality and the Obligation to Prevent International Humanitarian Law Violations: A Case Study of US Military Assistance in Russia-Ukraine War - Gregory Joshua Manogar; Diajeng Wulan Christianti (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2023)
Although international law forbids states to use force against each other, every state has an obligation to stop the ongoing violation of international humanitarian law. Consequently, the relevance of the traditional law of neutrality is questionable and often considered obsolete in contemporary armed conflict. The United States of America introduced the doctrine of qualified neutrality. The doctrine allows other states to do something when there is a threat or ongoing violations of the peace and security of humankind. The United States has commonly justified its military assistance to one of the warring parties using the doctrine as in the current Russia-Ukraine War. The United States provides vast military assistance to Ukraine, consisting of weapons and specialized military training to stop Russian aggression. This study aims to assess the qualified neutrality doctrine from an international law perspective and whether the United States can still preserve its neutral status or become a co-belligerent of Ukraine. This study argues that qualified neutrality will not change the status of a neutral state into co-belligerent if it does not involve any use of force measures or, otherwise, these measures shall fall within the framework of the UN Charter and require authorization from the UN.DOI: https://doi.org/10.22304/pjih.v10n1.a5